2018
DOI: 10.1089/jpm.2017.0696
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Six-Year Project to Enhance the Awareness of Community-Based Palliative Care on the Place of Death

Abstract: Object: To examine the clinical outcomes of a project to enhance the awareness of community-based palliative care (awareness-enhancing project), focusing on home death and care rates in communities.Methods: A single-center study on community-based intervention was conducted. The awareness-enhancing project, consisting of three intervention approaches (outreach, palliative care education for community-based medical professionals, and information-sharing tool use), was executed, and changes in the home death rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 19 publications
0
17
0
6
Order By: Relevance
“…Community home health care nurses are on the frontline and provide comprehensive patient/family-centered care, contributing to patient comfort, fewer hospitalizations, and higher home death rates, which are often desired by patients and serve as a clinical outcome in the community. 40 The majority of patients who need home-based PC live in lowincome and middle-income settings. These services should be a major health priority in those countries.…”
Section: Discussionmentioning
confidence: 99%
“…Community home health care nurses are on the frontline and provide comprehensive patient/family-centered care, contributing to patient comfort, fewer hospitalizations, and higher home death rates, which are often desired by patients and serve as a clinical outcome in the community. 40 The majority of patients who need home-based PC live in lowincome and middle-income settings. These services should be a major health priority in those countries.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing awareness of community-based palliative care has shown to impact on place of death. 20 A recent study suggested that the cost of provision of specialist community palliative care services may offset the cost of hospital-based end-of-life care by reduced acute hospital admissions and bed days to the public. 21 This suggests the need for further exploration of the relationship between local hospital resources especially in areas of low deprivation and the impact on place of death for various causes.…”
Section: Discussionmentioning
confidence: 99%
“…Av de inkluderte studiene var det en med randomisert kontrollert (RCT) (35) design, og en pilotstudie med to ulike studiefaser (36). Ellers inkluderte vi ni retrospektive tverrsnittstudier (4,8,13,(37)(38)(39)(40)(41)(42), og åtte kohortstudier (43)(44)(45)(46)(47)(48)(49)51). Alle studiene ble publisert mellom 2010 og 2020.…”
Section: Studieegenskaperunclassified